Molecular Detection of Virulence Factors of some Protozoan Infection Causing Diarrhea in Children in Waist Province - AL-Khalek, Esrai Jaleel Abd; Hraija, Baraa Abdulsalam (Iraqi Journal of Science, 2026)
Background: Intestinal parasite infections (IPIs) have significantly declined in recent decades, largely due to hygiene and health education improvements. Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum . This study aimed to achieve two key objectives: To diagnose these three parasites using nested PCR, and identify the most common virulence factors associated with each parasite (E. histolytica, G. lamblia, and C. parvum) in children using multiplex PCR. Material and methods: This cross-sectional study was conducted in Wasit province. A total number of 296 stool samples were randomly collected and examined, 96 samples of them from children (˂16 years) affected by diarrhea. Results: Nested PCR results revealed the following positivity rates for the three parasites: 82/96 (85.42%) positive for E. histolytica, 17/96 (17.71%) positive for G. lamblia, and 34/96 (35.42%) positive for C. parvum. Multiplex PCR analysis of virulence factors showed that, out of the 96 patients, 77 were positive for the cysteine proteinase gene, and 72 were positive for the amoeba pore c gene in E. histolytica. For G. lamblia, 17 out of 96 patients were positive for the cysteine proteinase gene and 17 were positive for the variant-specific surface protein gene. Finally, for C. parvum, 34 out of 96 patients were positive for the cysteine proteinase gene, and 34were positive for the 60 kDa glycoprotein gene. Conclusion: These findings suggest that virulence factors play a significant role in parasitic pathogenesis and are frequently involved in the initial pathogen-host interactions.